2008
DOI: 10.1016/j.socscimed.2008.06.030
|View full text |Cite
|
Sign up to set email alerts
|

The psychological impact of the Israel–Hezbollah War on Jews and Arabs in Israel: The impact of risk and resilience factors

Abstract: Although there is abundant evidence that mass traumas are associated with adverse mental health consequences, few studies have used nationally representative samples to examine the impact of war on civilians, and none have examined the impact of the Israel-Hezbollah War, which involved unprecedented levels of civilian trauma exposure from July 12-August 14, 2006. The aims of this study were to document probable post-traumatic stress disorder (PTSD), determined by the PTSD Symptom Scale and self-reported functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
86
2
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 143 publications
(96 citation statements)
references
References 38 publications
7
86
2
1
Order By: Relevance
“…A similar tendency can be found in studies conducted in Israel (e.g., Palmieri et al 2008). Recent studies have begun looking at the aftermath of war, as a crisis containing a potential for growth as well as distress and pathology (Levine et al 2008;O'Rourke et al 2008).…”
Section: Introductionsupporting
confidence: 71%
“…A similar tendency can be found in studies conducted in Israel (e.g., Palmieri et al 2008). Recent studies have begun looking at the aftermath of war, as a crisis containing a potential for growth as well as distress and pathology (Levine et al 2008;O'Rourke et al 2008).…”
Section: Introductionsupporting
confidence: 71%
“…Kumar et al (2007) also reported that women were nearly three times as likely as men to exhibit PTSD symptoms after the December 2004 tsunami in India. Lower educational level has been noted as a risk factor for PTSD in some studies (e.g., Lai et al, 2004;Palmieri, Canetti-Nisim, Galea, Johnson, & Hobfoll, 2008;van Griensven et al, 2006). The possible underlying mechanism is that lower educational level may be associated with lower resilience, including poorer coping skills, lower self-esteem, and lower insight, etc., which made victims have difficulties in recovering from trauma.…”
Section: Discussionmentioning
confidence: 99%
“…First, background and psychosocial data including psychosocial/economic status, previous exposure history, length of time since the trauma, and social support were unavailable for analysis. This data includes some factors that previously were found to be influential on risk and on manifestation of PTSD Neuner et al, 2004;Palmieri et al, 2008). The role of time elapsed since the trauma is controversial mainly in the context of ongoing exposure because there is not always a clear stressor that motivates the individual to seek help.…”
Section: Discussionmentioning
confidence: 99%